2019
DOI: 10.3389/fsurg.2019.00055
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Fusion Targeted vs. Systematic Prostate Biopsy–How Does the Biopsy Technique Affect Gleason Grade Concordance and Upgrading After Radical Prostatectomy?

Abstract: Introduction: MRI-targeted biopsy (TB) increases overall prostate-cancer (PCa) detection-rates and decreases the risk of insignificant PCa detection. However, the impact of these findings on the definite pathology after radical prostatectomy (RP) is under debate.Materials and Methods: Between 01/2014 and 12/2018, 366 patients undergoing prostate biopsy and RP were retrospectively analyzed. The correlation between biopsy Gleason-score (highest Gleason-score in a core) and the RP Gleason-score in patients underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…These observations do not completely agree with previous publications, where SB and TB were not compared within the same patient. For example, Rührup et al and Apfelbeck et al reported a concordance of between 46.7%–48.9% with SB alone [ 8 , 11 ]. Conversely, the upgrading rate in the study by Apfelbeck et al was invariably higher (46.7%).…”
Section: Discussionmentioning
confidence: 99%
“…These observations do not completely agree with previous publications, where SB and TB were not compared within the same patient. For example, Rührup et al and Apfelbeck et al reported a concordance of between 46.7%–48.9% with SB alone [ 8 , 11 ]. Conversely, the upgrading rate in the study by Apfelbeck et al was invariably higher (46.7%).…”
Section: Discussionmentioning
confidence: 99%
“…MRI‐targeted biopsies, which utilise previously taken MRI images of suspected cancer and fuse them with real‐time ultrasound images, are reported to be able to detect high‐grade cancers better than systematic biopsies and TRUS 6‐9,20,21 . However, several recent studies have reported a mismatch in the biopsy and radical prostatectomy Gleason Score 10,11,22 . Despite the improved detection of clinically significant cancers with MRI‐targeted biopsies, considerable disparity exists in the literature regarding MRI‐targeted biopsy's ability to better detect RP pathology in biopsy‐naive men over conventional TRUS biopsies 10,11,22 .…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9]20,21 However, several recent studies have reported a mismatch in the biopsy and radical prostatectomy Gleason Score. 10,11,22 Despite the improved detection of clinically significant cancers with MRI-targeted biopsies, considerable disparity exists in the literature regarding MRI-targeted biopsy's ability to better detect RP pathology in biopsy-naive men over conventional TRUS biopsies. 10,11,22 We performed this study in order to investigate if targeted prostate biopsy has a performance superior to untargeted biopsy in determining the optimal agreement between biopsy and surgical Gleason Score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations